Teacher competence frameworks in Hungary: A case study on the continuum of teacher learning. (11th July 2019) - Symeonidis, Vasileios
Abstract: The aim of this article is to examine the development and implementation of teacher competence frameworks in Hungary. Supported by European structural funds, Hungary introduced a teacher competence framework for initial teacher education in 2006 and another for the career promotion and appraisal of teachers in 2013. Employing the process tracing method, the article follows the evolution of teacher competence frameworks over time, based on a document analysis and expert interviews with policy officials and teacher educators. Findings show that the Hungarian teacher competence frameworks evolved as an outcome of a broader Europeanisation process in teacher education, on the one hand, and of internal political priorities, on the other. Strong political commitment was often linked to weak implementation capacities, so that dissatisfaction was created on the side of teachers. Depending on the way local actors use these frameworks, some perceive it as a way of limiting teacher autonomy, whilst others feel it promotes teacher professionalism.